Peritoneal dialysis as a life-saving procedure in an extremely low birth weight infant: case report and review of the literature - Çetinkaya, Merih; Ercan, Tuğba Erener; Yavuz, Sevgi; Özaydın, Seyithan (The Turkish Journal of Pediatrics, 2020)
Background. Acute kidney injury (AKI) is a common condition in the neonatal intensive care unit (NICU), particularly in preterm infants. Management of AKI in neonates is challenging. Peritoneal dialysis (PD) has been preferred as the most applicable modality in neonates when medical therapy fails. Case. A female infant was born at 24 and 4/7 weeks with a birth weight of 460 grams after an emergency cesarian section from a preeclamptic pregnacy. She developed AKI secondary to sepsis. A neonatal, straight single-cuff Tenckhoff catheter was inserted and PD was started on day 12. PD was discontinued after 6 days, on day 18 with adequate urine output and normalization of kidney function tests. However, the patient died on day 152 secondary to a nosocomial infection. Conclusion. To the best of our knowlegde, our case is the smallest infant in whom PD was performed succesfully with a PD catheter. PD is a relatively safe, effective and a feasible therapy in the neonatal population even in the smallest infants. PD may be a live-saving procedure in extremely low birth weight infants with severe AKI.